Positive plate and preparation method thereof, sodium-ion battery and power-related equipment

By adopting a multi-layer structure of single crystal mixed material and polyanionic material in the sodium ion battery positive electrode sheet, and performing partial coating and rolling treatment, the processing and electrical performance problems of the thick coated electrode sheet of polyanionic material are solved, and higher rate performance and longer cycle life are achieved.

CN119812218APending Publication Date: 2025-04-11深圳为方能源科技有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510164193.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing polyanionic material thick coated electrode sheets have processing problems such as coating cracking, rolling and breaking of belts, winding and material dropping, as well as electrical performance problems such as battery cell ratio difference and internal resistance lift.

Method used

The positive electrode sheet structure is adopted, including a substrate and a single crystal mixed material layer disposed on both sides of the substrate and a polyanionic material layer disposed on the single crystal mixed material layer, and the ratio performance and processing performance of the thick coated electrode sheet are improved by partial coating and rolling treatment.

Benefits of technology

By adding layered small single crystal hybrid materials, the specific capacity and electrochemical performance of polyanionic materials are improved, the failure rate during coating and rolling is reduced, and the cycle life and electrochemical performance of the battery cell are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812218A_ABST
    Figure CN119812218A_ABST
Patent Text Reader

Abstract

The invention provides a positive plate and a preparation method thereof, a sodium-ion battery and power-related equipment, and relates to the technical field of new energy. The positive plate provided by the invention comprises the base material, the single-crystal mixed material layers arranged on the two sides of the base material and the polyanion material layers arranged on the single-crystal mixed material layers, the polyanion material is low in specific capacity, the capacity is increased by adding the layered small single-crystal mixed material, and the single-crystal mixed material is stable in structure and good in rate capability, so that the capacity of the positive plate is improved. And the rate capability of the thick coated pole piece in a battery cell can be improved. The single crystal mixed material layer can also serve as a priming coat, and the problems of poor conductivity, insufficient binding power, low compaction and the like caused by direct contact between the polyanion material and the base material are solved. The first layer is coated with a layered small single crystal mixed material, so that the rate capability of the thick coated pole piece can be improved; and the second layer is coated with a polyanion material, and the problem of difficult wettability of thick coating can be improved due to large specific surface area and good liquid absorbability of the polyanion material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of new energy technology, and in particular to a positive electrode sheet and a preparation method thereof, a sodium ion battery and electrical equipment. Background Art

[0002] With the increase in the penetration rate of new energy power generation, the randomness and volatility of the power generation side are becoming increasingly severe. As a new source of regulation capacity, energy storage has accelerated the demand for installed capacity. Compared with lithium-ion batteries, industrialized sodium-ion batteries have obvious cost advantages. In addition, the safety performance, high and low temperature performance, and rate performance of sodium-ion batteries are better than those of lithium-ion batteries, and are expected to become an important supplement in the field of energy storage. Among the three major routes of sodium-ion battery positive electrode materials, polyanion compounds have stable structures, high cycle life, high thermal stability, and high operating voltage, making them the most suitable route for long-term energy storage.

[0003] At present, the specific capacity of polyanion materials is low, and the overall energy density of the battery is low. The overall energy density of sodium batteries can be improved by thickly coating the electrodes, but thickly coated electrodes have processing problems such as coating cracking, roller breakage, and winding material loss, as well as electrical performance problems such as poor cell rate and increased internal resistance that need to be solved. Summary of the invention

[0004] The purpose of the present application is to provide a positive electrode sheet and a preparation method thereof, a sodium ion battery and electrical equipment, aiming to solve the processing problems of existing thick-coated electrodes of polyanion materials such as coating cracking, rolling breakage, winding dropout, as well as electrical performance problems such as poor cell rate and increased internal resistance.

[0005] To achieve the above objectives, the present application provides a positive electrode sheet, please refer to Figure 1 , comprising: a substrate and a first active material layer (active material layer 1) disposed on both sides of the substrate and a second active material layer (active material layer 2) disposed on the first active material layer;

[0006] Wherein, the first active material layer includes a first active material; the second active material layer includes a second active material; the first active material is a single crystal hybrid material, and the second active material is a polyanion material.

[0007] In some embodiments, the compaction density of the first active material layer is 45% to 85% of the compaction density of the powder of the first active material, for example, it can be 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or any value between 45% and 85%, and the compaction density of the second active material layer is 50% to 70% of the compaction density of the first active material layer, for example, it can be 50%, 53%, 55%, 58%, 60%, 62%, 65%, 68%, 70% or any value between 50% and 70%.

[0008] In some embodiments, the ratio of the thickness of the second active material layer to the thickness of the first active material layer is 0.4 to 4, for example, it can be 0.4, 0.8, 1, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 1.9, 2, 2.5, 3, 3.5, 4 or any value between 0.4 and 4;

[0009] Preferably, the ratio of the thickness of the second active material layer to the thickness of the first active material layer is 1-2.

[0010] In some embodiments, the surfaces of the first active material layer and the second active material layer have uneven embossing; the embossing is a continuous pattern, or includes at least one of a plurality of dot-shaped, line-shaped, and surface-shaped patterns.

[0011] In some embodiments, the first active material layer further includes a first conductive agent and a first binder; the second active material layer further includes a second conductive agent and a second binder, and satisfies at least one of the following conditions:

[0012] A. The ratio of the mass of the second conductive agent to the mass of the first conductive agent is 1 to 50, for example, 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50 or any value between 1 and 50;

[0013] B. The ratio of the mass of the second binder to the mass of the first binder is 0.5-1, for example, 0.5, 0.6, 0.7, 0.8, 0.9, 1 or any value between 0.5 and 1.

[0014] In some embodiments, the particle size D50 of the first active substance is ≤6 μm, for example, it can be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm or any value ≤6 μm; and / or, the particle size D50 of the second active substance is ≤3 μm, for example, it can be 1 μm, 2 μm, 3 μm or any value ≤3 μm.

[0015] In some embodiments, at least one of the following conditions is met:

[0016] A. The chemical formula of the single crystal hybrid material is Na n [Mn x Fe y Ni z Li 1-x-y-z ]O2, where 0.8≤n<0.84, 0.5≤x<0.6, 0.08≤y≤0.15, 0.18≤z, 3.47≤x / z≤4.66;

[0017] B. The chemical formula of the polyanion material is Na3(VO x PO4)2F 3-2x , where 0≤x≤1;

[0018] C. The substrate is polyethylene terephthalate.

[0019] The present application also provides a method for preparing the above-mentioned positive electrode sheet, comprising:

[0020] Applying a first mixed slurry including a first active material on both sides of the substrate, and performing a first rolling press to obtain a semi-finished positive electrode sheet;

[0021] A second mixed slurry including a second active material is coated on both sides of the semi-finished positive electrode sheet, and a second rolling is performed to obtain the positive electrode sheet.

[0022] In some embodiments, the speeds of the first rolling and the second rolling are independently controlled at 5-30 m / min, for example, 5 m / min, 10 m / min, 15 m / min, 20 m / min, 25 m / min, 30 m / min or any value between 5-30 m / min, and the pressures of the first rolling and the second rolling are independently set to 3-10 T, for example, 3 T, 4 T, 5 T, 6 T, 7 T, 8 T, 9 T, 10 T or any value between 3-10 T;

[0023] Preferably, the first rolling is followed by a first embossing.

[0024] Preferably, the second rolling is followed by a second embossing.

[0025] Preferably, the speeds of the first embossing and the second embossing are independently controlled at 10-15 m / min, for example, they can be 10 m / min, 11 m / min, 12 m / min, 13 m / min, 14 m / min, 15 m / min or any value between 10-15 m / min, and the depths of the first embossing and the second embossing are independently controlled at 0.02 μm to 1 μm, for example, they can be 0.02 μm, 0.05 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm or any value between 0.02 μm and 1 μm.

[0026] The present application also provides a sodium ion battery, comprising the above-mentioned positive electrode sheet.

[0027] The present application also provides an electrical device, comprising the above-mentioned sodium ion battery.

[0028] Compared with the prior art, the beneficial effects of this application include:

[0029] The positive electrode provided by the present application includes a substrate and a single crystal hybrid material layer arranged on both sides of the substrate and a polyanion material layer arranged on the single crystal hybrid material layer. The polyanion material has a low specific capacity, and the capacity is increased by adding a layered small single crystal hybrid material. The single crystal hybrid material has a stable structure and good rate performance, which can increase the rate performance of the thick-coated electrode in the battery cell. The single crystal hybrid material layer can also serve as a primer layer, which improves the problems of poor conductivity, insufficient adhesion and low compaction caused by direct contact between the polyanion material and the substrate. The first layer is coated with a layered small single crystal hybrid material to improve the rate performance of the thick-coated electrode; the second layer is coated with a polyanion material, because it has a large specific surface area and good liquid absorption, it can improve the problem of difficult wettability of thick coating.

[0030] The preparation method of the positive electrode sheet provided in the present application divides the thick coating into two coating processes, which can effectively improve the problem of coating cracking, and divides the rolling pressing into two processes, which greatly reduces the problems of electrode piece breakage, particle crushing due to overpressure, and large rebound of the electrode piece after pressing. It not only improves production efficiency, but also avoids the deterioration of electrical performance caused by particle crushing, large rebound of the electrode piece, poor wettability of the electrode piece due to overpressure electrolyte, etc., and greatly improves the cycle life of the battery cell.

[0031] Furthermore, the first rolling process is embossed, which can increase the surface roughness of the pole piece, and the second coating layer has better adhesion to the first coating layer, which greatly improves the problem of powder shedding in thick coating. The second rolling process is embossed, which can improve the problem of difficult wettability in thick coating.

[0032] The sodium ion battery and electrical equipment provided in the present application can increase capacity, improve rate performance, increase cycle life, and have excellent chemical properties by using the positive electrode sheet of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.

[0034] Figure 1 This is a schematic diagram of the structure of the positive electrode sheet of this application. DETAILED DESCRIPTION

[0035] As used herein:

[0036] "Prepared from" is synonymous with "comprising." As used herein, the terms "comprising," "including," "having," "containing," or any other variation thereof, are intended to cover a non-exclusive inclusion. For example, a composition, process, method, article, or apparatus that comprises the listed elements is not necessarily limited to only those elements but may include other elements not expressly listed or inherent to such composition, process, method, article, or apparatus.

[0037] The conjunction "consisting of excludes any unspecified element, step, or component. If used in a claim, this phrase renders the claim closed-ended so that it does not include materials other than those described, except for conventional impurities associated therewith. When the phrase "consisting of" appears in a clause of the body of a claim rather than immediately following the subject matter, it limits only the elements described in that clause; other elements are not excluded from the claim as a whole.

[0038] When an amount, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values ​​and lower preferred values, this should be understood as specifically disclosing all ranges formed by any pairing of any range upper limit or preferred value with any range lower limit or preferred value, regardless of whether the range is disclosed separately. For example, when a range of "1 to 5" is disclosed, the described range should be interpreted as including ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described in this article, unless otherwise stated, the range is intended to include its end values ​​and all integers and fractions within the range.

[0039] In these examples, parts and percentages are by mass unless otherwise indicated.

[0040] "Parts by mass" refers to the basic unit of measurement for expressing the mass ratio of multiple components. 1 part can represent any unit mass, such as 1g or 2.689g. If we say that the mass of component A is a parts and the mass of component B is b parts, it means the ratio of the mass of component A to the mass of component B is a:b. Alternatively, it means that the mass of component A is aK and the mass of component B is bK (K is an arbitrary number, indicating a multiple factor). It should not be misunderstood that, unlike the mass parts, the sum of the mass of all components is not limited to 100 parts.

[0041] "And / or" is used to indicate that one or both of the stated situations may occur, for example, A and / or B includes (A and B) and (A or B).

[0042] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0043] Example 1

[0044] This embodiment provides a positive electrode sheet, and the preparation method thereof includes the following steps:

[0045] a. Layered single crystal material Na 0.83 [Mn 0.55 Fe 0.125 Ni 0.225 Li 0.1 ]O2, a conductive agent and a binder are mixed, and an appropriate amount of an organic solvent is added and stirred evenly to obtain a mixed slurry 1, wherein the binder is polyvinylidene fluoride (PVDF), and the conductive agent is Ketjen black compounded graphene (mass ratio 7:3); the organic solvent is NMP; the main material accounts for 92 parts, PVDF accounts for 5 parts, and the conductive agent of Ketjen black compounded graphene accounts for 3 parts in total. NMP is used to adjust the solid content and control the solid content at 60%.

[0046] b. The polyanion material Na3(VO 0.7 PO4)2F 1.6 , a conductive agent, and a binder are mixed, an appropriate amount of an organic solvent is added, and the mixture is stirred evenly to obtain a mixed slurry 2, wherein the binder is polyvinylidene fluoride (PVDF), and the conductive agent is Ketjen black compounded graphene (mass ratio 7:3); the organic solvent is NMP; the main material accounts for 94 parts, PVDF accounts for 4 parts, and the conductive agent of Ketjen black compounded graphene accounts for 2 parts in total. NMP is used to adjust the solid content to control the solid content at 50%.

[0047] c. The mixed slurry 1 is evenly coated on both sides of the polyethylene terephthalate (PET) substrate. The coating thickness of the mixed slurry 1 is 50% of the total thickness of the electrode coating design.

[0048] d. The positive electrode sheet obtained in step c is roll-pressed, and the compaction density of the first active material layer is controlled to be 80% of the compaction density of the powder of the layered single crystal material, which is 2.56 g / cc. The pressed electrode sheet is embossed, wherein the rolling speed is controlled to be 15 m / min, and the pressure is set at 5.4 T; the embossing speed is controlled to be 12 m / min, and the embossing depth is controlled to be 0.08 μm.

[0049] e. The mixed slurry 2 is evenly coated on both sides of the pole piece obtained in step d, and the coating thickness of the mixed slurry 2 is 50% of the total designed coating thickness of the pole piece.

[0050] f. The positive electrode sheet obtained in step e was roll-pressed, and the compaction density of the second active material layer was controlled at 1.75 g / cc. After rolling, embossing was performed, wherein the rolling speed was controlled at 12 m / min and the pressure was set at 6.6 T; the embossing speed was controlled at 10 m / min and the embossing depth was controlled at 0.08 μm.

[0051] g. Cut and slice the electrode obtained in step f to obtain the positive electrode of Example 1.

[0052] This embodiment also provides a sodium ion battery, the preparation method of which comprises the following steps:

[0053] The positive electrode sheet of Example 1, a hard carbon negative electrode sheet, a 16 μm ceramic separator, and a 1M NaPF6 / (EC+PC+DMC) electrolyte (the volume ratio of EC, PC, and DMC is 1:1:1) are used to make a sodium ion battery through winding-packaging-injection-formation and other processes.

[0054] Example 2

[0055] This embodiment provides a positive electrode sheet, and the preparation method thereof is different from that of Embodiment 1 only in that: the coating thickness of the mixed slurry 1 in step c is 70% of the total designed coating thickness of the electrode sheet, and the coating thickness of the mixed slurry 2 in step e is 30% of the total designed coating thickness of the electrode sheet, and the other steps are the same as those of Embodiment 1.

[0056] Example 3

[0057] This embodiment provides a positive electrode sheet, and the preparation method thereof is different from that of Embodiment 1 only in that: the coating thickness of the mixed slurry 1 in step c is 20% of the total designed coating thickness of the electrode sheet, and the coating thickness of the mixed slurry 2 in step e is 80% of the total designed coating thickness of the electrode sheet, and the other steps are the same as those of Embodiment 1.

[0058] Example 4

[0059] This embodiment provides a positive electrode sheet, and the preparation method thereof differs from that of Embodiment 1 only in that: in step d, the positive electrode sheet obtained in step c is roll-pressed, and the compaction density of the first active material layer is controlled at 80% of the compaction density of the powder of the layered single crystal material. The pressed electrode sheet is not embossed and directly proceeds to the next process, and the other steps are the same as those of Embodiment 1.

[0060] Example 5

[0061] This embodiment provides a positive electrode sheet, and the preparation method thereof is different from that of embodiment 1 only in that: in step f, the positive electrode sheet obtained in step e is roll-pressed, and after the rolling is completed, no embossing treatment is performed, and the next step is directly performed, and the other steps are the same as those of embodiment 1.

[0062] Comparative Example 1

[0063] This comparative example provides a positive electrode sheet, and the preparation method thereof is different from that of Example 1 only in that: the positive electrode active material in the mixed slurry 1 in step a is a polyanion material Na3(VO 0.7 PO4)2F 1.6 In step b, the positive electrode active material in the mixed slurry 2 is a layered single crystal material Na 0.83 [Mn 0.55 Fe 0.125 Ni 0.225 Li 0.1 ]O2, the other steps are the same as in Example 1.

[0064] Comparative Example 2

[0065] This comparative example provides a positive electrode sheet, and the preparation method thereof is different from that of Example 1 only in that: the positive electrode active material in the mixed slurry 1 in step a is a polyanion material Na3(VO 0.7 PO4)2F 1.6 In step b, the positive electrode active material in the mixed slurry 2 is a polyanion material Na3(VO 0.7 PO4)2F 1.6 , the other steps are the same as those in Example 1.

[0066] Comparative Example 3

[0067] This comparative example provides a positive electrode sheet, and the preparation method thereof comprises the following steps:

[0068] a. The polyanion material Na3(VO 0.7 PO4)2F 1.6 , a conductive agent, and a binder are mixed, an appropriate amount of an organic solvent is added, and the mixture is stirred evenly to obtain a mixed slurry 1, wherein the binder is polyvinylidene fluoride (PVDF), and the conductive agent is Ketjen black compounded graphene (mass ratio 7:3); the organic solvent is NMP; the main material accounts for 92 parts, PVDF accounts for 5 parts, and the conductive agent of Ketjen black compounded graphene accounts for 3 parts in total. NMP is used to adjust the solid content to control the solid content at 60%.

[0069] b. The mixed slurry 1 is evenly coated on both sides of the PET substrate. The coating thickness of the mixed slurry 1 is 100% of the total thickness of the electrode coating design.

[0070] c. Roll the positive electrode sheet obtained in step b and emboss the pressed electrode sheet, wherein the rolling speed is controlled at 5-30 m / min and the pressure is set at 5.4 T; the embossing speed is controlled at 12 m / min and the embossing depth is controlled at 0.08 μm.

[0071] d. The electrode sheet obtained in step c is cut and sliced ​​to obtain the positive electrode sheet of comparative example 3.

[0072] This comparative example also provides a sodium ion battery, and its preparation method is the same as that of Example 1.

[0073] Comparative Example 4

[0074] This comparative example provides a positive electrode sheet, and its preparation method is different from that of Example 1 only in that: in step d, the positive electrode sheet obtained in step c is roll-pressed, the compaction density of the first active material layer is controlled to be 100% of the compaction density of the powder of the layered single crystal material, the pressed electrode sheet is embossed, and the other steps are the same as those of Example 1.

[0075] Comparative Example 5

[0076] This comparative example provides a positive electrode sheet, and the preparation method thereof is different from that of Example 1 only in that in step d, the positive electrode sheet obtained in step c is not subjected to rolling and embossing treatment, and the next step is directly performed, and the other steps are the same as those of Example 1.

[0077] The positive electrode sheets of the above embodiments and comparative examples were tested respectively, and the testing methods are as follows:

[0078] Compacted density: Compacted density = coating surface density / coating thickness;

[0079] 24H pole piece rebound: 24H pole piece rebound = (24H pole piece thickness - initial pole piece thickness) / initial pole piece thickness, tested using a micrometer;

[0080] Diaphragm resistance: directly tested by diaphragm resistance meter;

[0081] 20H electrode wettability: The electrode wettability is judged based on the amount of liquid absorbed by the electrode within 24 hours. When the liquid absorption coefficient (liquid absorption / theoretical capacity) ≥ 80% of the designed liquid injection coefficient, the electrode wettability is determined to be good; when the liquid absorption coefficient (liquid absorption / theoretical capacity) < 80% of the designed liquid injection coefficient, the electrode wettability is determined to be poor.

[0082] The test results of the positive electrode sheets of various embodiments and comparative examples are shown in Table 1.

[0083] Table 1. Test results of positive plates of various embodiments and comparative examples

[0084]

[0085] The electrochemical performance tests were performed on the sodium ion batteries of the above embodiments and comparative examples respectively, and the test methods were as follows:

[0086] Battery internal resistance: directly tested by ACR tester;

[0087] First effect: first discharge capacity / first charge capacity, current is 0.2C (1C is 3000mAh), charge and discharge temperature is 25℃;

[0088] 3C discharge: At 25℃, the battery is left standing for 5min, 0.2C cccv 4.2V to 0.05C, left for 5min, 0.2C DCto 2V, left for 5min; 0.2C cccv 4.2V to 0.05C, left for 5min, 3C DC to2V, left for 5min, calculate the 3C discharge capacity / 0.2C discharge capacity is the 3C capacity retention rate (1C = 3000mAh);

[0089] Energy efficiency: discharge energy / charge energy.

[0090] The test results of the electrochemical performance of the sodium ion batteries of the embodiments and comparative examples are shown in Table 2.

[0091] Table 2. Electrochemical performance of sodium ion batteries of various embodiments and comparative examples

[0092]

[0093] According to Table 1 and Table 2, the electrical properties of the positive electrode sheets of Examples 1 to 5 using the scheme of the present application are better than those of the comparative scheme, but the coating thickness of the mixed slurry 2 of Example 3 is thicker, which will affect the processing performance of the positive electrode sheet, affect the manufacturability and product yield, but have little effect on the electrical performance; the positive electrode sheet of Example 4 is not embossed after coating the mixed slurry 1, which will also affect the processing performance of the positive electrode sheet, while the positive electrode sheet of Example 5 is not embossed after coating the mixed slurry 2, which will not affect the processing performance.

[0094] In the solutions of Comparative Examples 1, 2 and 3, the polyanion material Na3(VO3) is in direct contact with the substrate. 0.7 PO4)2F 1.6 , the material dropped seriously during the preparation process, and the positive electrode sheet could not be obtained, indicating that the processing performance of the polyanion material is poor. The compaction density of the mixed slurry 1 of the positive electrode sheet of Comparative Example 4 is 100% of the compaction density of the powder of the layered single crystal material. As a result, some particles were broken during the preparation process, affecting the electrochemical performance of the positive electrode sheet. The positive electrode sheet of Comparative Example 5 was not subjected to roller pressing and embossing treatment after coating the mixed slurry 1, and the tape broke frequently during the preparation process, and the processing performance was poor.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

[0096] In addition, those skilled in the art will appreciate that, although some embodiments herein include certain features included in other embodiments but not other features, the combination of features of different embodiments is meant to be within the scope of the present application and form different embodiments. For example, in the above claims, any one of the claimed embodiments may be used in any combination. The information disclosed in this background technology section is intended only to deepen the understanding of the overall background technology of the present application and should not be regarded as an admission or in any form of implication that the information constitutes prior art known to those skilled in the art.

Claims

1. A positive electrode sheet, characterized in that: include: A substrate, a first active material layer disposed on both sides of the substrate, and a second active material layer disposed on the first active material layer; Wherein, the first active material layer includes a first active material; the second active material layer includes a second active material; the first active material is a single crystal hybrid material, and the second active material is a polyanion material.

2. The positive electrode sheet according to claim 1, characterized in that: At least one of the following conditions is met: A. the compaction density of the first active material layer is 45% to 85% of the compaction density of the powder of the first active material; B. the compaction density of the second active material layer is 50% to 70% of the compaction density of the first active material layer; C. the ratio of the thickness of the second active material layer to the thickness of the first active material layer is 0.4 to 4; Preferably, the ratio of the thickness of the second active material layer to the thickness of the first active material layer is 1-2.

3. The positive electrode sheet according to claim 1, characterized in that: The surface of the first active material layer and / or the second active material layer has uneven embossing; Optionally, the embossing is a continuous pattern, or includes at least one of a plurality of dot-shaped, line-shaped, and surface-shaped patterns.

4. The positive electrode sheet according to claim 1, characterized in that: The first active material layer further includes a first conductive agent and a first binder; the second active material layer further includes a second conductive agent and a second binder, and satisfies at least one of the following conditions: A. the ratio of the mass of the second conductive agent to the mass of the first conductive agent is 1 to 50; B. The ratio of the mass of the second binder to the mass of the first binder is 0.5-1.

5. The positive electrode sheet according to claim 1, characterized in that: The particle size D50 of the first active material is ≤6 μm; and / or the particle size D50 of the second active material is ≤3 μm.

6. The positive electrode sheet according to claim 1, characterized in that: At least one of the following conditions is met: A. The chemical formula of the single crystal hybrid material is Na n [Mn x Fe y Ni z Li 1-x-y-z ]O2, where 0.8≤n<0.84, 0.5≤x<0.6, 0.08≤y≤0.15, 0.18≤z, 3.47≤x / z≤4.66; B. The chemical formula of the polyanion material is Na3(VO x PO4)2F 3-2x , where 0≤x≤1; C. The substrate is polyethylene terephthalate.

7. A method for preparing a positive electrode sheet according to any one of claims 1 to 6, characterized in that: include: Applying a first mixed slurry including a first active material on both sides of the substrate, and performing a first rolling press to obtain a semi-finished positive electrode sheet; A second mixed slurry including a second active material is coated on both sides of the semi-finished positive electrode sheet, and a second rolling is performed to obtain the positive electrode sheet.

8. The method for preparing a positive electrode sheet according to claim 7, characterized in that: The speeds of the first rolling and the second rolling are independently controlled at 5-30 m / min, and the pressures of the first rolling and the second rolling are independently set to 3-10 T. Preferably, the first rolling is followed by a first embossing. Preferably, the second rolling is followed by a second embossing. Preferably, the speeds of the first embossing and the second embossing are independently controlled at 10-15 m / min, and the depths of the first embossing and the second embossing are independently controlled at 0.02 μm to 1 μm.

9. A sodium ion battery, characterized in that: A positive electrode sheet comprising any one of claims 1 to 6.

10. An electrical equipment, characterized in that: Including the sodium ion battery as described in claim 9.